2023
DOI: 10.21203/rs.3.rs-3131787/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial Heterogeneity in Population Health Impacts and Vulnerability to Compound Climate Hazards: Extreme Heat and Wildfire Smoke in California

Abstract: Extreme heat and wildfire smoke events are increasingly co-occurring in the context of climate change, especially in California. Extreme heat and wildfire smoke may have synergistic effects on population health that vary over space. We leveraged high-resolution satellite and monitoring data to quantify spatially varying compound exposures to extreme heat and wildfire smoke in California (2006–2019) at ZIP code level. We found synergistic effects between extreme heat and wildfire smoke on cardiorespiratory hosp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…For each respiratory binary response (asthma, LRTI, or URTI) and corresponding case-crossover dataset, we applied a conditional logistic model to estimate the odds ratio of the effect of PM 2.5 at 3 temperature levels (colder, median, hotter) and within 4 seasons ( Chen et al 2023 ). The conditional logistic model accounts for the case/control matching by comparing the exposures of each matched case and control, and calculating a weighted average across all matched sets (Di et al 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each respiratory binary response (asthma, LRTI, or URTI) and corresponding case-crossover dataset, we applied a conditional logistic model to estimate the odds ratio of the effect of PM 2.5 at 3 temperature levels (colder, median, hotter) and within 4 seasons ( Chen et al 2023 ). The conditional logistic model accounts for the case/control matching by comparing the exposures of each matched case and control, and calculating a weighted average across all matched sets (Di et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review of several studies, almost entirely in urban populations, indicate sufficient findings of moderate quality to support synergistic effects for temperature and air pollution ( Anenberg et al 2020 ), although such evidence for pediatric respiratory outcomes is extremely limited ( Winquist et al 2014 ). Assessment of these questions in rural communities also is limited, but a recent case crossover study in California for all age cardiorespiratory hospitalization showed strong evidence for a synergistic effect between wildfire specific PM 2.5 and extreme heat ( Chen et al 2023 ). Although the authors did not specifically evaluate rurality, they found weaker interactions between temperature and air pollution in counties with higher education attainment, health insurance coverage, income, and automobile ownership, possibly due to greater capacity to reduce harmful exposures in individuals of higher socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…To explore finer scale spatially varying effects, we used a previously developed withincommunity matched design to estimate the ZCTA-specific effect of wildfire PM 2.5 on the risk of daily respiratory acute care utilization (C. Chen et al, 2023). Specifically, we identified matched controls for each day exposed to wildfire smoke as non-wildfire smoke days of the same year and ZCTA, and within the window of 30 calendar days before or after the wildfire smoke day.…”
Section: Within-community Matched Design Coupled With Spatial Bayesia...mentioning
confidence: 99%
“…To evaluate the robustness of the within-community matched design and spatial BHM, we conducted a sensitivity analysis using informative priors employed in previous studies for the sill and nugget in the spatial BHM, which are inverse gamma distributions (2 for shape and 1/starting value for scale) (C. Chen et al, 2023). This sensitivity analysis tested the robustness of the spatial BHM towards prior specification and the informative priors used here give more weight to our interpretation of the empirical semivariogram while the flat priors in main analysis were more data-driven.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
See 1 more Smart Citation